Prevalence and determinants of medication adherence among hypertensive patients: An institution-based cross-sectional study - Azaz Bin Sharif; Syed Sharaf Ahmed Chowdhury; Md. Zakir Hossain; Md. Anwar Hossain; Ahmed Hossain; Hasan Mahmud Reza (PLoS ONE, 2025)
Background Adherence to antihypertensive medication is a key management strategy for hypertension, which gives rise to the necessity to get a clear picture of medication adherence among patients with hypertension in Bangladesh. This study aims to determine the prevalence of antihypertensive medication adherence and its associated factors among patients with hypertension receiving treatments at a Hypertension Center in Bangladesh. Methods An institution-based cross-sectional study was conducted on 352 adult patients with hypertension registered in the Rangpur Hypertension and Research Center. The outcome variable for the study was medication adherence to the antihypertensive drug, which was measured using the Morisky Medication Adherence Scale (MMAS-8). Descriptive analysis was conducted to show the distribution of the study participants, Pearson’s chi-square test was applied to explore associations between categorical response and explanatory variables, and bivariable and multivariable logistic regression analyses were conducted to explore factors associated with medication adherence. All statistical analyses were conducted using Stata version 17.0. Results The prevalence of good medication adherence among patients with hypertension in the HRC, R was 54.83%. Among various reasons for taking the medicine irregularly, forgetfulness (20.29%) was the most common cause reported by the participants, followed by a busy work schedule (7.71%). Among the study participants, married patients were found to have higher medicine adherence (AOR= 3.81; 95% CI: 1.34–10.89) than unmarried patients. Compared to patients who had hypertension for less than or equal to 5 years, patients suffering from hypertension for 6–10 years had 68% (AOR= 0.32; 95% CI: 0.11–0.95) and patients suffering for more than 10 years had 72% (AOR= 0.28; 95% CI: 0.09–0.84) lower odds of medicine adherence, respectively. Patients who were diagnosed by non-professionals had 81% (AOR= 0.19; 95% CI: 0.06–0.61) lower odds of medicine adherence compared to the patients who were diagnosed by health professionals. Conclusion This study observed low medication adherence among patients with hypertension, where forgetfulness and a busy work schedule were reported to be the primary reasons for such non-adherence. Patients who are not married, who have been suffering for a long, and who have not been diagnosed by a health professional manifested as significant influencing factors for non-adherence.